Field-induced spin liquid in the decorated square-kagome antiferromagnet nabokoite $${{{\rm{KCu}}}}_{7}{{{\rm{TeO}}}}_{4}{({{{\rm{SO}}}}_{4})}_{5}{{\rm{Cl}}}$$ KCu 7 TeO 4 ( SO 4 ) 5 Cl - Matías G. Gonzalez; Yasir Iqbal; Johannes Reuther; Harald O. Jeschke (Communications Materials)
Abstract Quantum antiferromagnets based on the square-kagome lattice are proving to be a fertile platform for realizing nontrivial phenomena in frustrated magnetism. Recently, several decorated square-kagome compounds of the nabokoite family have been synthesized, allowing for experimental exploration of model Hamiltonians. Here, we carry out a theoretical analysis of $${{{\rm{KCu}}}}_{7}{{{\rm{TeO}}}}_{4}{({{{\rm{SO}}}}_{4})}_{5}{{\rm{Cl}}}$$ KCu 7 TeO 4 ( SO 4 ) 5 Cl nabokoite using a Heisenberg Hamiltonian derived from density functional theory energy mapping. We employ classical Monte Carlo simulations to explain the two transitions experimentally observed in the low-temperature magnetization curve. Interestingly, the intermediate-field phase is also found in a purely two-dimensional model and is described by a spin liquid featuring subextensive degeneracy with a ferrimagnetic component. We show that this phase can be approximated by a checkerboard lattice in a magnetic field. Finally, we assess the effects of quantum fluctuations in zero fields using the pseudo-Majorana functional renormalization group method.